Effect of coupling agent on the mechanical properties of flame retardant PP/ATH nanocomposites - Sabaruddin, Fatimah A’thiyah; Samat, Noorasikin (Trans Tech Publications, Switzerland, 2013)
Polymer nanocomposites containing polypropylene (PP) as the polymer matrix and nanofiller aluminium hydroxide (ATH) as the flame retardant filler were compounded with various loading of maleic anhydride grafted polypropylene, MAPP (0, 1, 2, 3, 5 wt %). All materials were mixed using melt mixing process and were further prepared using an injection moulding machine. The mechanical performances of the samples were characterized using tensile and impact tests. Improvements were observed for the tensile and impact properties of the PP/ATH samples after being loaded with MAPP. MAPP loading of 1 wt % was determined to be the optimum content of coupling agent addition as this loading enabled the best performance of the nanocomposite in tensile and impact tests. Different morphologies of the fracture surfaces for all samples were characterized using FESEM analysis.